Selection of ICT tools for the development of high school students' research competencies in specialized chemistry training - Pavlo Nechypurenko; Serhiy Semerikov; Tetyana Selivanova; Tetyana Shenayeva (Academy of Cognitive and Natural Sciences, 2021)
The article analyzed the place of information and communication technologies and learning tools in specialized chemistry training. The development of research competencies of high school students as one of the important results of specialized training in chemistry is considered. The analysis and systematization of ICT tools to ensure compliance with the principles of specialized chemistry training is made. The choice of ICT tools for the implementation of specialized chemistry training and development of high school students' research competencies in specialized chemistry training had substantiated. The results of research aimed at determining the feasibility of using certain ICT tools to develop of high school students' research competencies in specialized chemistry training are presented.